1979
DOI: 10.1007/bf00846666
|View full text |Cite
|
Sign up to set email alerts
|

Generalizability and durability of treatment effects in an intervention program for coronary-prone (type A) managers

Abstract: To test the reliability and durability of positive treatment effects obtained in a type A intervention project for healthy managers, the analysis was extended to data available from a third treatment group (a special behavior therapy group for participants eliminated from the main sample because of manifestations of clinical CHD) and to measures obtained 6 months following the end of treatment. Immediately after treatment all three groups showed a similar pattern of improvement, although the two behavior thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…It is encourag ing that several studies utilized Applied Analysis of Behavior to expedite the intervention process or recognized that the demands of the behav ior change process should be recognized and dealt with (e.g. giving up Type A behavior may be very anxiety provoking) (41,42,47). Some re searchers not only recognized the demand characteristics of the interven tion, but attempted to control for their contaminating effect on out come (44,46).…”
Section: Review Of Selected Current Researchmentioning
confidence: 99%
“…It is encourag ing that several studies utilized Applied Analysis of Behavior to expedite the intervention process or recognized that the demands of the behav ior change process should be recognized and dealt with (e.g. giving up Type A behavior may be very anxiety provoking) (41,42,47). Some re searchers not only recognized the demand characteristics of the interven tion, but attempted to control for their contaminating effect on out come (44,46).…”
Section: Review Of Selected Current Researchmentioning
confidence: 99%
“…Although behavioral approaches with self-control components seem to be most effective, the best method for intervention has not been identified. Roskies (1979) indicated that it was important to distinguish key pathogenic elements in the TABP. The hard-driving/competitive factor and the speed/impatience factor showed the highest association with CHD among the Type A dimensions (Matthews, Glass, Rosenman, & Bortner, 1977).…”
mentioning
confidence: 99%
“…Few Type A intervention studies have been conducted (2)(3)(4)(5)(6)(7). Those Received for publication May 20, 1983; revision received February 21, 1984. done used the same general approach.…”
mentioning
confidence: 99%
“…Those Received for publication May 20, 1983; revision received February 21, 1984. done used the same general approach. Following the hypothesis that the pathway leading from behavior to CHD is the chronic sympathetic nervous system arousal accompanying chronic Type A hyperreactivity (1), targets of treatment were to reduce the frequency, intensity, and duration of physiologic (2)(3)(4)(5)(6)(7), cognitive (4)(5)(6)(7), and/or behavioral (2,6) hyperreactivity. The most common research design evaluated the effectiveness with which a variety of therapeutic approaches [e.g., physical relaxation (2)(3)(4)(5)(6), cognitive self-instruction (7), insight (4,5), group support (6)] reduced Type A hyperreactivity in small groups of subjects (from 14 to 42) over short periods of time (from 5 to 14 hr).…”
mentioning
confidence: 99%
See 1 more Smart Citation